Effect of phosphodiesterase-5 inhibition with Tadalafil on SystEmic Right VEntricular size and function – A multi-center, double-blind, randomized, placebo-controlled clinical trial – SERVE trial - Rational and design. (15th September 2017) - Tobler, Daniel; Bouchardy, Judith; Reto, Engel; Heg, Dik; Müller, Christian; Frenk, André; Gabriel, Harald; Schwitter, Jürg; Rutz, Tobias; Buechel, Ronny R.; Willhelm, Matthias; Trachsel, Lukas; et al.
Abstract: Background: Patients with a systemic right ventricle (RV) have a compromised late outcome caused by ventricular dysfunction. Standard medical heart failure therapy has not been shown to improve RV function and survival in these patients. Phosphodiesterase (PDE)-5 inhibition increases contractility in experimental models of RV hypertrophy, but not in the normal RV. In clinical practice, the effects of PDE-5 inhibition on systemic RV function and exercise capacity in adults with a systemic RV have not been tested. Methods: The SERVE protocol is a double-blind, randomized placebo-controlled multicenter superiority trial to study the effect of PDE-5 inhibition with Tadalafil on RV volumes and function in patients with either D-transposition of the great arteries repaired with an atrial switch procedure or with congenitally corrected transposition of the great arteries. Tadalafil 20 mg or placebo will be given over a study period of 3 years. The primary endpoint is the change in mean end-systolic RV volumes from baseline to study end at 3 years of follow-up (or at the time of permanent discontinuation of the randomized treatment if stopped before 3- years of follow-up), and will be measured by cardiovascular magnetic resonance imaging (CMR) or by cardiac computed tomography in patients with contraindications for CMR. Secondary endpoints are changes in RV ejection fraction, VO2max and NT-proBNP. Conclusion: The objective of this study is to assess the effect of PDE-5 inhibition with Tadalafil on RV size and function, exercise capacity and neurohumoral activation in adults with a systemic RV over a 3-year follow-up period.